Provision or limitation? Digital technology experiences of students with disabilities at the University of Dhaka (Teacher’s World: Journal of Education and Research, 2023)
As digital technology is becoming an integral part of education systems, there are substantial risks of a digital divide among the students reaching beyond the divide influenced by different socio-economic backgrounds. Despite there being constitutionally endorsed equality for all Bangladeshis, students with disability often face difficulties in accessing their fundamental human rights, including education. Notwithstanding the nationwide aim for inclusive education throughout, very few students with disability can achieve even limited success, which prompts questions about the system, the process and the provisions. With the qualitative methodology at the core to capture and analyse detailed data in depth and with sufficient trustworthiness, this paper investigated the institutional provisions of technology available for students with disabilities at the University of Dhaka. It particularly focuses on the provisions of digital technology support services of the university and the perceived impact of those provisions on the living and learning of students with disabilities. This study used a multiple case study approach for generating data using semi-structured interviews and FGD. A deductive thematic analysis approach was used for data analysis. The findings systematically indicate that, in most cases, the underdeveloped provision of services is not a result of resource scarcity but mainly a consequence of the perceived unimportance or ‘negligence’ of the needs of students with disability. And these are the results of collective normalised norms and ideals that, by design, exclude such students. The findings also depicted how technology uses helped students with disability to empower themselves and to become primarily self-dependent. However, at the same time, some service provisions and attitudes of relevant personnel led them to opt out of availing equal opportunities to learn and to thrive.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.83-94